Phase-Shifted Bragg Grating based on Silicon-on-Insulator Nanowire - QIN Zhibin; YAO Fei; XIAO Jing; WEI Qiqin (Guangtongxin yanjiu)
Electronic integrated chips based on metal interconnections face increasing challenges, including crosstalk, delay, heat dissipation, and power consumption, making it difficult to meet the growing demand for data processing. Optoelectronic integration is considered to be the next generation interconnect technology. As this technology continuous to evolve, the industry's requirements for the size and performance of optoelectronic devices are becoming increasingly demanding.【Objective】To address the device size and loss of the Bragg phase shift grating, this paper proposes a Bragg phase shift grating based on Silicon-on-Insulator (SOI) nanowires.【Methods】By leveraging photolithography technology, periodic grooves are created on silicon nanowires to construct the grating structure, effectively reducing the transmission loss of optical signals. In order to verify the performance of the Bragg phase-shifted grating, the transmission modes and characteristics of the device are analyzed and studied using the finite element method and the finite-difference time-domain method under conditions with an incident wavelength range of 1 400 to 1 600 nm. Additionally, to obtain the best structural parameters of the Bragg phase-shift grating, the Q factor is introduced as the optimization target parameter.【Results】The results show that the Bragg phase shift grating has excellent wavelength selection performance in the wavelength range of 1 400～1 600 nm, and has a ultra-low transmission loss. Notably, when the maximum Q factor is 159, the Bragg phase shift grating achieves the best performance, with the grating period N of 60.【Conclusion】This grating offers significant advantages over surface plasmon-based Bragg phase shift gratings in terms of manufacturing cost and transmission loss of optical signal. As a result, it has wide applications in dense wavelength division multiplexing, biological sensing, filtering, and other related fields.